2017
DOI: 10.1098/rsos.160969
|View full text |Cite
|
Sign up to set email alerts
|

The importance of temperature fluctuations in understanding mosquito population dynamics and malaria risk

Abstract: Temperature is a key environmental driver of Anopheles mosquito population dynamics; understanding its central role is important for these malaria vectors. Mosquito population responses to temperature fluctuations, though important across the life history, are poorly understood at a population level. We used stage-structured, temperature-dependent delay-differential equations to conduct a detailed exploration of the impacts of diurnal and annual temperature fluctuations on mosquito population dynamics. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 48 publications
7
83
0
Order By: Relevance
“…Furthermore, most of the aforementioned modelling studies used constant or mean monthly temperature in their formulation. Recent studies have shown that the incorporation of daily (diurnal) temperature fluctuations in the model may also affect predictions [12,13,74].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most of the aforementioned modelling studies used constant or mean monthly temperature in their formulation. Recent studies have shown that the incorporation of daily (diurnal) temperature fluctuations in the model may also affect predictions [12,13,74].…”
Section: Introductionmentioning
confidence: 99%
“…Exposed vectors are recruited into the infectious class according to RVIfalse(tfalse)=left0,leftwhen4.pttτEIP,leftRVE(tτEIP)prefixexp(δAτEIP),leftt>τEIP.Although τEIP can be formulated to fluctuate with diurnal and seasonal temperature variation (Beck‐Johnson et al. , ), we assume constant temperatures so that τEIP is constant. The fraction of exposed mosquitoes surviving long enough to become infectious is given by the exponential term in equation .…”
Section: Methodsmentioning
confidence: 99%
“…) in response to seasonal changes in temperature and rainfall (Beck‐Johnson et al. , reviewed in Eikenberry and Gumel ). Further, interventions aimed at mosquitoes (e.g., insecticide treated nets) are widespread and have contributed to substantial declines in malaria infections (Bhatt et al.…”
mentioning
confidence: 99%
“…Impacts of temperature on population dynamics and vector competence are complex (Beck-Johnson et al, 2013). Mosquitoes are sensitive to temperature throughout their life cycle and it has been shown by mathematical modeling studies that the fluctuations in diurnal temperatures may affect the mosquito life cycle and malaria transmission (Beck-Johnson et al, 2017). Carrington et al, in a study conducted in northwest Thailand have found that large diurnal temperature range (DTR) adversely affects mosquito biology by extending immature development phase, lowered larval survival and reduced female reproductive capacity (Carrington et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%